2021
DOI: 10.21203/rs.3.rs-1016518/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Isoeugenol Affects Expression Pattern of Conidial Hydrophobin Gene RodA and Transcriptional Regulators MedA and SomA Responsible for Adherence and Biofilm Formation in Aspergillus fumigatus

Abstract: Aspergillus fumigatus is one of the major pathogenic fungal species, causing life-threatening infections. Due to a limited spectrum of available antifungals, exploration of new drug targets as well as potential antifungal molecules has become pertinent. Rodlet layer plays an important role in adherence of fungal conidia to hydrophobic cell surfaces in host, which also leads to A. fumigatus biofilm formation, contributing factor to fungal pathogenicity. From decades, natural sources have been known for the deve… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…In our study, the overexpression of the MDR4 gene suggested that this gene is linked with ITC resistance and after eugenol treatment gene expression was decreased. Further, transcription regulatory genes MedA and SomA were downregulated in all the eugenol-treated ARAF isolates except B19 and R03 for MedA gene expression and similar results were reported by Gupta et al (2022) for the downregulation of MedA and SomA genes in presence of isoeugenol. Further, mfsC gene expression analysis showed that the gene was downregulated in the four treated ARAF isolates (B19, RT28, B03 and RB01).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In our study, the overexpression of the MDR4 gene suggested that this gene is linked with ITC resistance and after eugenol treatment gene expression was decreased. Further, transcription regulatory genes MedA and SomA were downregulated in all the eugenol-treated ARAF isolates except B19 and R03 for MedA gene expression and similar results were reported by Gupta et al (2022) for the downregulation of MedA and SomA genes in presence of isoeugenol. Further, mfsC gene expression analysis showed that the gene was downregulated in the four treated ARAF isolates (B19, RT28, B03 and RB01).…”
Section: Discussionsupporting
confidence: 85%
“…Ten azole-resistant A.fumigatus isolates (eugenol-treated and untreated) along with a susceptible A.fumigatus (ATCC 46645; control) isolates were investigated for the expression analysis of the genes of interest by quantitative real time PCR (qRT-PCR; Gupta et al, 2022). Two micrograms of total RNA were reverse transcribed into first-stand cDNA using the Hi-cDNA synthesis kit (HiMedia, India) by following the manufacturer's recommendations.…”
Section: Quantification Of Gene Expression By Qrt-pcrmentioning
confidence: 99%
“…The expression of the genes of interest was quantified by quantitative real time-PCR (qRT-PCR) (Gupta et al, 2019(Gupta et al, , 2022. Mycelial cultures were harvested, and RNA was extracted using TRIzol ™ reagent (Invitrogen).…”
Section: Gene Expression Analysismentioning
confidence: 99%